Intention to Use Takaful (Islamic Insurance): Case Study in Tanzania - Suleiman, Fatma Hemed (SMART Insight, 2025)
This study shows the factors influencing intention to adopts takaful in Tanzania by applying the Amos on SEM model which is Structural Equation Modelling by using 100 data collected from respondent and the key factors are attitude, awareness, cost & benefit, compliance and reputation. The result show that attitude, cost & benefit and awareness are positive significant with the intention to use takaful in Tanzania while the compliance and reputation has no significant to the intention to use takaful in Tanzania because it has insignificant. The measurement model it shown to be good validity and reliability which is supported by the Cronbach’s Alpha scores so the model fit indices and confirm the adequacy of the model. the finding recommending the public awareness, fostering positive attitude and benefits of takaful are the main factor to increase the adaption but not only that but also the study suggesting on the takaful provider and regulator to have a good regulation on takaful and ensure the transparency on the working so as to influence the people to intent to use the Islamic insurance in Tanzania.